CORPORATE GOVERNANCE DAN MANAJEMEN LABA (Students' Journal of Accounting and Banking, 2013)
This study aimed to analyze the influence of corporate governance and earnings management. Corporate governance is a control mechanism to regulate and manage the business with a view to increasing prosperity and corporate accountability.This study uses 23 manufacturing companies going public are listed on the Indonesia Stock Exchange from 2008-2011. Sampling technique using purposive sampling method. The independent variable is independent board of commisioners, the number of board meetings, independent of audit committee, the number of audit committee meetings and the external auditor as an instrument of good corporate governance. While the dependent variable is earnings management.The analysis of this study result that the board of commissioners, the number of board meetings, and the number of audit committee meetings is not significantly affected by the negative direction. Independent of audit committee and external auditors is positive but not significant effect.Keywords: independent board of commisioners, number of board meetings, independent of audit committee, the number of the audit committee meetings, external auditors, earnings management.